The Lean Healthcare Implementation Self‐Assessment Instrument (LHISI): A Principles‐Based Survey Instrument to Assess Lean Implementation. (20th August 2020) - Rundall, T.; Blodgett, J.; Reponen, E.; Shortell, S.
Abstract : Research Objective: Lean implementation assessment is needed to understand the depth and breadth of Lean deployment and guide organizations in strengthening Lean implementation and its potential to improve organizational performance. To assist health care leaders to understand the extent to which Lean management has been implemented in their organizations, we developed the Lean Healthcare Implementation Self‐Assessment Instrument (LHISI), a 34‐item survey instrument that assesses Lean implementation across six dimensions. Study Design: Following a review of extant measures of Lean implementation, an initial list of 101 items was compiled and reviewed by Lean implementation experts, reflecting behaviors linked to 14 principles of Lean management from the Shingo and 4P models of Lean. Two rounds of item selection surveys were completed by health care managers and clinicians to identify the most important items, which were included in LHISI version 1 (V1). Managers and clinicians in 7 different organizations completed two rounds of V1 pilot testing used to perform test‐retest analyses, exploratory factor analysis (EFA), and other statistical tests to develop V2. Finally, managers and clinicians at two large teaching hospitals pilot tested V2, and their responses were divided into half and used for EFA and confirmatory factor analysis (CFA), respectively. Population Studied: Item selection and pilot testing surveys were completed by managers and clinicians in seven health care organizations currently implementing Lean management. The two rounds of item selection included 36 and 39 respondents; V1 pilot testing included 232 respondents (including 34 retests); and V2 pilot testing included 914 respondents. Principal Findings: Expert review and two rounds of item selection testing reduced the number of survey items from 101 to the 48 items included in V1. Each item reflects an important core principle of Lean (eg, In my unit/department, work processes are standardized; across my hospital/clinic, leaders at all levels create a safe environment for exposing problems; and in my unit/department, frontline staff use visual displays to understand their unit's performance). V1 pilot testing analyses suggested removal of 5 items: 2 items did not load on a factor in exploratory factor analysis, and 3 items had insufficient test‐retest reliability (the remaining items had Pearson's r 0.72‐0.85). Consequently, LHISI V2 included 43 items, and the 914 responses were randomly divided and used for EFA and CFA. EFA demonstrated six underlying factors encompassing 34 items (9 items did not fit well with any factor): organizational culture (10 items), commitment to Lean (7 items), standard work (5 items), huddles (4 items), unit culture (4 items), and visual management (4 items). Each of the subscales demonstrates good internal consistency, with Cronbach alphas ranging from .89 to .97. CFA model fit comparisons supported the above six‐factor model over single factor and seven‐factor models. Conclusions: The 34‐item LHISI demonstrates good content validity, internal consistency, test‐retest reliability, and appropriate factor clusters. Implications for Policy or Practice: The LHISI provides an accessible way for health care leaders to assess Lean implementation in their organization and to identify targets for improvement. Ongoing research will further explore the characteristics of the instrument, including the relationship between LHISI scores and performance.